Antibiotic prescribing for acute respiratory tract infections 12 months after communication and CRP training: A randomized trial - Little, P; Stuart, B; Francis, N; Douglas, E; Tonkin-Crine, S; Anthierens, S; Cals, J; Melbye, H; Santer, M; Moore, M; Coenen, S; Butler, C; et al. (Annals of Family Medicine, 2019)
Purpose C-reactive-protein (CRP) is useful for diagnosis of lower respiratory tract infections (RTIs). A large international trial documented that Internet-based training in CRP point-of-care testing, in enhanced communication skills, or both reduced antibiotic prescribing at 3 months, with risk ratios (RRs) of 0.68, 0.53, 0.38, respectively. We report the longer-term impact in this trial. Methods A total of 246 general practices in 6 countries were cluster-randomized to usual care, Internet-based training on CRP point-of-care testing, Internet-based training on enhanced communication skills and interactive booklet, or both interventions combined. The main outcome was antibiotic prescribing for RTIs after 12 months. Results Of 228 practices providing 3-month data, 74% provided 12-month data, with no demonstrable attrition bias. Between 3 months and 12 months, prescribing for RTIs decreased with usual care (from 58% to 51%), but increased with CRP training (from 35% to 43%) and with both interventions combined (from 32% to 45%); at 12 months, the adjusted RRs compared with usual care were 0.75 (95% CI, 0.51-1.00) and 0.70 (95% CI, 0.49-0.93), respectively. Between 3 months and 12 months, the reduction in prescribing with communication training was maintained (41% and 40%, with an RR at 12 months of 0.70 [95% CI, 0.49-0.94]). Although materials were provided for free, clinicians seldom used booklets and rarely used CRP point-of-care testing. Communication training, but not CRP training, remained efficacious for reducing prescribing for lower RTIs (RR = 0.7195% CI, 0.45-0.99, and RR = 0.76; 95% CI, 0.47-1.06, respectively), whereas both remained efficacious for reducing prescribing for upper RTIs (RR = 0.60; 95% CI, 0.37-0.94, and RR = 0.58; 95% CI, 0.36-0.92, respectively). Conclusion Internet-based training in enhanced communication skills remains effective in the longer term for reducing antibiotic prescribing. The early improvement seen with CRP training wanes, and this training becomes ineffective for lower RTIs, the only current indication for using CRP testing.